Sex-Differences in the Oxygenation Levels of Intercostal and Vastus Lateralis Muscles During Incremental Exercise - Espinosa-Ramírez, Maximiliano; Moya-Gallardo, Eduardo; Araya-Román, Felipe; Riquelme-Sánchez, Santiago; Rodriguez-García, Guido; Reid, W. Darlene; Viscor, Ginés; Araneda, Oscar F.; Gabrielli, Luigi; Contreras-Briceño, Felipe (Frontiers in Physiology, 2021)
This study aimed to examine sex differences in oxygen saturation in respiratory (SmO2-m.intercostales) and locomotor muscles (SmO2-m.vastus lateralis) while performing physical exercise. Twenty-five (12 women) healthy and physically active participants were evaluated during an incremental test with a cycle ergometer, while ventilatory variables (lung ventilation [V ̇E], tidal volume [Vt], and respiratory rate [RR]) were acquired through the breath-by-breath method. SmO2 was acquired using the MOXY devices on the m.intercostales and m.vastus lateralis. A two-way ANOVA (sex × time) indicated that women showed a greater significant decrease of SmO2-m.intercostales, and men showed a greater significant decrease of SmO2-m.vastus lateralis. Additionally, women reached a higher level of ΔSmO2-m.intercostales normalized to V ̇E (L·min-1) (p<0.001), whereas men had a higher level of ΔSmO2-m.vastus lateralis normalized to peak workload-to-weight (watts·kg-1, PtW) (p=0.049), as confirmed by Student’s t-test. During an incremental physical exercise, women experienced a greater cost of breathing, reflected by greater deoxygenation of the respiratory muscles, whereas men had a higher peripheral load, indicated by greater deoxygenation of the locomotor muscles.